Numerical investigations on the damage tolerance of adhesively bonded pultruded GFRP joints with adhesion defects - Fame,CM; Wu,C; Feng,P; Tam,L-H (Composite Structures, 2022)
Adhesive bonding has gained increasing acceptance in joining pultruded glass fiber reinforced polymer (GFRP) sections. However, one of the major issues hindering the widespread application of adhesive bonding in building and construction industries is the difficulty in predicting the mechanical behavior of the joints in the presence of adhesion defects. This paper investigates the damage tolerance of the adhesively bonded pultruded GFRP double-strap joints under quasi-static tensile loading using finite element analysis. Defects of various locations (along the bond length), sizes, and numbers were embedded within the bondline. A two-dimensional (2D) stress analysis was conducted to assess the effects of the bondline defects on the out-of-plane displacement, stress distribution, and peak stresses of the joints. Three-dimensional (3D) progressive damage models were further developed to predict residual joint capacity and provide insights into the effects of the adhesion defects on the damage mechanism of the joints. The progressive damage model uses the cohesive zone model (CZM) to simulate progressive interlaminar damage within the adherends as well as adhesive-FRP interface debonding. The proposed FE model was validated with published experimental data, and an excellent correlation was found between experimental and numerical results. The validated model was then used in a parametric study to assess the effects of design parameters such as adhesive types (from highly brittle to highly ductile) and joint geometry (adhesive chamfering, adherend chamfering, and recessing) on the damage tolerance of adhesively bonded joints. This paper also reports a comparative study on the damage tolerance between GFRP double-strap, single-strap, and single-step joints. The stress analysis results revealed that the presence of the bondline defects could increase the out-of-plane displacement of the adherends and the peak shear and peel stresses at the overlap ends. High-stress concent